Low-temperature phosphorescence of dicyanoacetylene in rare gas solids - Turowski, M.; Crépin, C.; Couturier-Tamburelli, I.; Piétri, N.; Kołos, R. (Физика низких температур, 2012)
A strong visible ã³Σu⁺ – X̃¹Σg⁺ luminescence was observed upon the UV excitation of cryogenic rare gas (argon, krypton, and xenon) matrices doped with dicyanoacetylene (NC₄N). Spectra and lifetimes of this phosphorescence have been measured. A detailed analysis of resolved vibronic bands is presented.